Novel Reflections on the Autonomy and Responsibility of Science - Hempel, Fabian (Frontiers in Research Metrics and Analytics, 2021)
This paper explores how cultural understandings of the autonomy and responsibility of science in modern society are manifested in two contemporary science novels about research misconduct in biomedical research. In doing so, it looks at several facets of the societal impact of and on public and private biomedical research, especially with respect to changing authority relations and their epistemic and institutional consequences. The analysis focuses on the multi-layered ways in which social and epistemic interests are treated in Allegra Goodman’s Intuition and Jennifer Rohn’s The Honest Look. Goodman’s novel demonstrates how, intensified by the economization of science, internal cultural and institutional aspects of the scientific field enable social configurations that, among others, encourage scientific malpractice and lead to the delay of research projects epistemically and socially worth pursuing. In contrast, Rohn’s novel exemplifies the corrosion of the ideal scientific ethos by profit-driven practices in private-sector biomedical sciences. The concluding discussion juxtaposes these findings with pertinent contemporary phenomena in modern science systems to provide a more substantial understanding of the interpenetration between science and other social spheres.